Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s11069-022-05577-4
|View full text |Cite
|
Sign up to set email alerts
|

The severity of heat and cold waves amplified by high relative humidity in humid subtropical basins: a case study in the Gan River Basin, China

Abstract: High relative humidity (RH) and temperature extremes can occur simultaneously and persist for periods of time, resulting in serious harm to human health, especially in humid regions. Here, the Gan River Basin was used as a case study to investigate the characteristics of heat and cold waves using the apparent temperature (combined air temperature and RH) of the observed and ERA5 reanalysis datasets. Heat waves showed an increasing trend from 1961 to 2018 (particularly from 1997 to 2018), whereas during the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Based on the CDF, HECEs are categorized into four grades: mild (50%-100%), moderate (25%-50%), severe (10%-25%) and extreme (<10%). [Colour figure can be viewed at wileyonlinelibrary.com] the normalized intensity of all the HECEs, as reported by Zhang et al (2023a). This robust association suggested that higher levels of water vapour lead to a heightened intensity of HECEs.…”
Section: The Characteristics Of Heces With Varying Intensitiessupporting
confidence: 57%
See 3 more Smart Citations
“…Based on the CDF, HECEs are categorized into four grades: mild (50%-100%), moderate (25%-50%), severe (10%-25%) and extreme (<10%). [Colour figure can be viewed at wileyonlinelibrary.com] the normalized intensity of all the HECEs, as reported by Zhang et al (2023a). This robust association suggested that higher levels of water vapour lead to a heightened intensity of HECEs.…”
Section: The Characteristics Of Heces With Varying Intensitiessupporting
confidence: 57%
“…To consider the role of water vapour, here, a given day was identified as an HECE when the WBGT fell below the 10th percentile. The 10th percentile was calculated for each calendar day using daily WBGT within a 3-day half-window centred on the calendar day from 1959 to 2020 and smoothed by applying a 31-day moving average to eliminate highfrequency noise (He et al, 2023;Zhang et al, 2023a). For an occurrence to be classified as an HECE, it must persist for a minimum of three consecutive days to filter short events caused by local temperature fluctuations.…”
Section: Definition Of Humidity-related Extreme Cold Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, like many experiments involving temperature control variables, such constant sub-zero temperature scenarios are rarely encountered in actual strawberry cultivation, which often involves protective measures such as greenhouses or plastic tunnels. Lowtemperature events, such as cold waves, in major strawberry-producing regions globally typically last for no more than 10 days [30,31]. Inspired by prior research, we hypothesize that non-lethal daytime dynamic chilling exposures may have different effects on the pho-tosynthetic system activity in different photoperiod types of strawberries.…”
Section: Introductionmentioning
confidence: 89%